2023
DOI: 10.37689/acta-ape/2023ar000881
|View full text |Cite
|
Sign up to set email alerts
|

Fadiga e sono em trabalhadores de enfermagem intensivistas na pandemia COVID-19

Abstract: Conflitos de interesse: nada a declarar. ResumoObjetivo: Analisar a relação entre fadiga, qualidade do sono, variáveis de saúde e laborais em trabalhadores de enfermagem de terapias intensivas, na pandemia COVID-19.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 21 publications
2
4
0
Order By: Relevance
“…With regard to sleep quality, this study showed that the sample of hospital nurses had poor overall sleep quality, a finding consistent with other studies conducted both internationally and in Brazil [31][32][33][34]. Specifically, among nurses working in the emergency department, one study found a 66% prevalence of poor musculoskeletal disorders than their counterparts in other departments.…”
Section: Discussionsupporting
confidence: 88%
“…With regard to sleep quality, this study showed that the sample of hospital nurses had poor overall sleep quality, a finding consistent with other studies conducted both internationally and in Brazil [31][32][33][34]. Specifically, among nurses working in the emergency department, one study found a 66% prevalence of poor musculoskeletal disorders than their counterparts in other departments.…”
Section: Discussionsupporting
confidence: 88%
“…Most participants were classified as poor sleepers (74.4%), which is similar to findings described in previous studies, 33 34 35 36 with small differences regarding the prevalence of poor sleep quality in comparison to some surveys. This difference may be explained by the professional categories in the sample analyzed.…”
Section: Discussionsupporting
confidence: 88%
“…A Brazilian study found a predominance of poor sleep quality among nurses (72%) and nursing technicians (88%). 36 Another study conducted with nurses in Ethiopia found that 75% had poor sleep quality. 35 In the present investigation, poor sleep quality was also found among nursing staff, with the worse rate among nursing technicians/assistants (86%).…”
Section: Discussionmentioning
confidence: 99%
“…It involves three types of energy resources: physical (involving muscle movement), mental (involving cognitive processing), and emotional (involving emotion regulation and expression). 10 Professional contexts that are usually related to fatigue as there is a high likelihood of workers developing fatigue include hospitals, [11][12][13] pharmaceutical services, 14 and teaching 15 .…”
Section: /14mentioning
confidence: 99%
“…Thus, the educational context of ERT in the Covid-19 pandemic and the challenges faced by nurse educators, for which many were unprepared or had no training, indicated the need to study the fatigue phenomenon and the variables that may influence the health of teaching workers more in-depth. Even though there are studies addressing this phenomenon, [11][12][13][14][15] no studies have been identified thus far associating fully or partially online classes during the Covid-19 pandemic with work-related fatigue among nurse educators at public universities.…”
Section: /14mentioning
confidence: 99%